5 + 1 5 + 2 + 5 − 2 − 3 − 2 2 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution Brian:)
Log in to reply
Where'd you get that question? ASAT?
Log in to reply
Nope it was given to me by my cousin. I guess he goes to ALLEN so it must be from his maths module.
Thanks! Nice problem. :)
@Racchit Jain , i remembered this question is copied from SOF imo workbook class 9 ch-1 q.6 :-)
Idk, maybe, coaching institutes copy problems from books, so I guess so :)
Problem Loading...
Note Loading...
Set Loading...
Note first that ( 5 + 2 + 5 − 2 ) 2 =
( 5 + 2 ) + ( 5 − 2 ) + 2 ( 5 + 2 ) ( 5 − 2 ) = 2 5 + 2 5 − 4 = 2 ( 5 + 1 ) .
Next note that 3 − 2 2 = 2 − 2 2 + 1 = ( 2 ) 2 − 2 2 + 1 = ( 2 − 1 ) 2 .
The given expression can then be written as
5 + 1 2 ( 5 + 1 ) − ( 2 − 1 ) 2 = 2 − ( 2 − 1 ) = 1 .